ANALYZING EFFECT OF AGE AND SEX DIFFERENCES ON PROSOCIAL BEHAVIOR OF PRESCHOOL CHILDREN - Sibel YOLERİ (Fırat University, 2019)
In this study, it is aimed to evaluate preschool children’s prosocial behaviors according to teachers’ views. The sample group of this study comprised of 116, 5-6 year old children (girls= 53, boys= 63). Participants were recruited from eight classrooms in six early childhood centers located in the Uşak city center. A Demographic Information Form and Prosocial Behavior Scale-Teacher Form were used to collect the data. The Mann-Whitney U test is used for the statistical analysis. As a result of the study, gender statistically has a significant effect on prosocial behaviors. Also, children’s prosocial behaviors did not differ in significance level in terms of statistics according to age variable.